PENGARUH SUBTITUSI EKSTRAK KULIT BUAH NAGA MERAH TERHADAP KUALITAS PUTU AYU - Wahyuni, Mega; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
Utilization of red dragon fruit extract in food processed is still small. Dragon fruit skin has high nutritional value. The purpose of this research is to analyze the effect of substitution of red dragon fruit extract as much as 35%, 50% and 65% to the quality of putu ayu which include volume, shape, color, aroma, texture and taste. This type of research is purely experimental using a completely randomized design method. Types of data used are primary data sourced from 30 semi-trained panelists who provide answers to the questionnaire (organoleptic test format). The data that have been obtained then tabulated in the form of tables and conducted analysis of variants (ANAVA). If there is a significant different Duncan test is done. The results showed there is a real effect on the color quality. While the quality of volume, rectangular jagged shapes in the middle, a neat shape, same shape, aroma, smooth texture and soft and sweet and savory taste there is no significant effect difference. It can be concluded that the best percentage is in substitution of red dragon fruit skin extract as much as 65%.Key word : red dragon fruit extract, Putu Ayu, Quality